Prevalence and molecular characterization of Wolbachia in field-collected Aedes albopictus, Anopheles sinensis, Armigeres subalbatus, Culex pipiens and Cx. tritaeniorhynchus in China - Yi Yang; Yifan He; Guoding Zhu; Jilei Zhang; Zaicheng Gong; Siyang Huang; Guangwu Lu; Yalan Peng; Yining Meng; Xiaoli Hao; Chengming Wang; Jie Sun; et al. (Public Library of Science (PLoS), 2021)
Wolbachia are maternally transmitted intracellular bacteria that can naturally and artificially infect arthropods and nematodes. Recently, they were applied to control the spread of mosquito-borne pathogens by causing cytoplasmic incompatibility (CI) between germ cells of females and males. The ability of Wolbachia to induce CI is based on the prevalence and polymorphism of Wolbachia in natural populations of mosquitoes. In this study, we screened the natural infection level and diversity of Wolbachia in field-collected mosquitoes from 25 provinces of China based on partial sequence of Wolbachia surface protein (wsp) gene and multilocus sequence typing (MLST). Among the samples, 2489 mosquitoes were captured from 24 provinces between July and September, 2014 and the remaining 1025 mosquitoes were collected month-by-month in Yangzhou, Jiangsu province between September 2013 and August 2014. Our results showed that the presence of Wolbachia was observed in mosquitoes of Aedes albopictus (97.1%, 331/341), Armigeres subalbatus (95.8%, 481/502), Culex pipiens (87.0%, 1525/1752), Cx. tritaeniorhynchus (17.1%, 14/82), but not Anopheles sinensis (n = 88). Phylogenetic analysis indicated that high polymorphism of wsp and MLST loci was observed in Ae. albopictus mosquitoes, while no or low polymorphisms were in Ar. subalbatus and Cx. pipiens mosquitoes. A total of 12 unique mutations of deduced amino acid were identified in the wsp sequences obtained in this study, including four mutations in Wolbachia supergroup A and eight mutations in supergroup B. This study revealed the prevalence and polymorphism of Wolbachia in mosquitoes in large-scale regions of China and will provide some useful information when performing Wolbachia-based mosquito biocontrol strategies in China. Author summary The mosquitoes Aedes albopictus, Anopheles sinensis, Armigeres subalbatus, Culex pipiens and Cx. tritaeniorhynchus are native to China and the major vectors in the transmission of arboviruses, protozoans and nematodes. Recently, an innovative biocontrol strategy has been developed and evaluated based on the ability of Wolbachia to induce cytoplasmic incompatibility (CI), as well as interfere with the infection and replication of pathogens. Since the ability to induce CI largely depends on the density and diversity of Wolbachia, we investigated and characterized the natural infection of Wolbachia in above-mentioned five species of field-collected mosquitoes in 25 provinces of China. The results showed that the positive rates of Wolbachia infection were high in mosquitoes of Ae. albopictus, Ar. subalbatus and Cx. pipiens in large-scale regions of China and low in Cx. tritaeniorhynchus in Guizhou province. Phylogenetic analysis based on Wolbachia surface protein (wsp) gene and five multilocus sequence typing (MLST) loci indicated the high polymorphism of Wolbachia in Ae. albopictus, and low polymorphisms in Ar. subalbatus and Cx. pipiens. This finding contributes to the understanding of the nationwide distribution of Wolbachia and the potential application of this biocontrol strategy in China.